Azacitidine for the treatment of relapsed and refractory AML in older patients. Issue 2 (February 2015) - Itzykson, Raphael; Thépot, Sylvain; Berthon, Céline; Delaunay, Jacques; Bouscary, Didier; Cluzeau, Thomas; Turlure, Pascal; Prébet, Thomas; Dartigeas, Caroline; Marolleau, Jean-Pierre; Recher, Christian; Plantier, Isabelle; et al.
Highlights Azacitidine is feasible in relapsed/refractory AML patients older than 50 years. Overall response rate was 17% including 10% complete remissions. Median overall survival was 8.4 months. Outcome was better in patients with intermediate risk cytogenetics and few peripheral blasts.